Stability of Imported Commercial Fish Oils (Soft Gel) in East Java - Sugeng Heri Suseno; Agoes Mardiono Jacoeb; Dudu Abdulatip (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Commercial fish oils (soft gel) have been widely traded in Indonesia, especially in East Java.The aimof this research was to determine the quality and stability of fish oils (soft gel) in East Java examined bySchaal oven method and to determine the amount of fatty acids in the commercial fish oil. The stabilityof the commercial fish oil was determined based on peroxide value, anisidine value, and total oxidationafter the oils were stored at 40oC for 6 days. The experimental design used in this research was completelyRandomized Design (CRD) with a treatment time of storage (H-0, H-2, H-4 and H-6). The quality of thecommercial fish oils was in accordance with IFOS on the parameters of the FFA, peroxide value, anisidin,and the total oxidation.The stability test results showed the fish oil quality decreased over time and onlyanisidine value was still met the IFOS standards. Sample S4 was found containing the highest amount ofomega 3 ada EPA, while S3 contained the highest amount of DHA.